A Pragmatist Defence of Classical Financial Accounting Research. (19th February 2013) - Rutherford, Brian A.
Abstract : One reason for the disdain in which classical financial accounting research has come to held by many in the scholarly community is its allegedly insufficiently scientific nature. While many have defended classical research or provided critiques of post‐classical paradigms, the motivation for this paper is different. It offers an epistemologically robust underpinning for the approaches and methods of classical financial accounting research that restores its claim to legitimacy as a rigorous, systematic and empirically grounded means of acquiring knowledge. This underpinning is derived from classical philosophical pragmatism and, principally, from the writings of John Dewey. The objective is to show that classical approaches are capable of yielding serviceable, theoretically based solutions to problems in accounting practice.